Anti-Migratory Activity of Brazilin Chemodiversification on Breast Cancer Cells - Alberto Hernández-Moreno; Dania A. Nava-Tapia; Miriam D. Zuñiga-Eulogio; Jorge Bello-Martínez; Monserrat Olea-Flores; Tadeo Hernández-Moreno; Mario Ordoñez; Ana E. Zacapala-Gómez; Miguel A. Mendoza-Catalán; Napoleón Navarro-Tito (Scientia Pharmaceutica)
Breast cancer is the most common and the leading cause of cancer death in women worldwide; treating invasive breast carcinomas is challenging due to the side effects of chemotherapeutics. Compounds isolated from natural sources have been proposed as potential molecules for cancer therapy; for instance, the homoisoflavonoid brazilin has shown pharmacological properties, including anti-tumoral and anti-inflammatory activities. In this study, we isolated brazilin from the heartwood of Haematoxylum brasiletto; then, we performed a semi-synthesis by adding three methyl or acetyl groups to the core structure of brazilin. We confirmed the identity of brazilin and its derivatives by spectroscopic data (1H NMR and 13C NMR) and measured their purity by optical rotation. Then, we analyzed the effects of brazilin and its derivatives in three mammary gland-derived cell lines: the TNBC MDA-MB-231, the ERα(+) MCF7, and the non-tumorigenic MCF10A. We evaluated the cell viability by MTT assays, cell migration by wound-healing assays, and focal adhesion kinase (FAK) activation by Western blot. Regarding biological assays, the MTT assay showed that these compounds showed cytotoxic effects on the MCF7 and MDA-MB-231 breast cancer cells at 20 µM but was not toxic in non-tumorigenic MCF10A mammary epithelial cells. Specifically, the greatest effects found from treatment with the compounds were in the MDA-MB-231 cell line, where the IC50 of brazilin was 49.92 μM, and for MCF7, the brazilin-(OAc)3 was 49.97 μM. These effects were dose- and time-dependent, as well as being associated with a decrease in the levels of cell migration and FAK activation.